2005
DOI: 10.1002/bit.20399
|View full text |Cite
|
Sign up to set email alerts
|

Display of lipase on the cell surface of Escherichia coli using OprF as an anchor and its application to enantioselective resolution in organic solvent

Abstract: We have developed a new cell surface display system using a major outer membrane protein of Pseudomonas aeruginosa OprF as an anchoring motif. Pseudomonas fluorescens SIK W1 lipase gene was fused to the truncated oprF gene by C-terminal deletion fusion strategy. The truncated OprF-lipase fusion protein was successfully displayed on the surface of Escherichia coli. Localization of the truncated OprF-lipase fusion protein was confirmed by western blot analysis, immunofluorescence microscopy, and whole-cell lipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…To date, the expression systems for display of heterologous proteins on the surface of microorganisms have attained considerable progress in various applications in biotechnology and microbiology, for example whole-cell biocatalysis, vaccines vehicles, peptide library screening, biosensors, environmental bioadsorbents, and antibody production (Lee et al, 2003;Richins et al, 1997;Samuelson et al, 2002;Ståhl and Uhlén, 1997;Wernérus and Ståhl, 2004). In display systems for gram-negative bacteria, various anchoring motifs have been employed including outer membrane proteins (Francisco et al, 1992;Lee et al, 2005), lipoproteins, and ice nucleation protein (INP) (Jung et al, 1998a,b), poly-g-glutamate (PGA) synthetase complex (Narita et al, 2006). In fact, INP is a more promising display system for displaying enzymes (Jung et al, 1998a,b;Kim et al, 2000;Li et al, 2004;Shimazu et al, 2001aShimazu et al, ,b, 2003Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…To date, the expression systems for display of heterologous proteins on the surface of microorganisms have attained considerable progress in various applications in biotechnology and microbiology, for example whole-cell biocatalysis, vaccines vehicles, peptide library screening, biosensors, environmental bioadsorbents, and antibody production (Lee et al, 2003;Richins et al, 1997;Samuelson et al, 2002;Ståhl and Uhlén, 1997;Wernérus and Ståhl, 2004). In display systems for gram-negative bacteria, various anchoring motifs have been employed including outer membrane proteins (Francisco et al, 1992;Lee et al, 2005), lipoproteins, and ice nucleation protein (INP) (Jung et al, 1998a,b), poly-g-glutamate (PGA) synthetase complex (Narita et al, 2006). In fact, INP is a more promising display system for displaying enzymes (Jung et al, 1998a,b;Kim et al, 2000;Li et al, 2004;Shimazu et al, 2001aShimazu et al, ,b, 2003Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…It was estimated that 1,534 lipase molecules were displayed per cell of P. putida harboring pMO188PL. This value is quite high compared with the value for E. coli cells displaying lipase using OmpC or OprF as an anchoring motif (14,15). It was also found that induction with a low IPTG FIG.…”
Section: Discussionmentioning
confidence: 89%
“…This property should be useful for enantioselective biocatalysis in an organic solvent. Lipases have been used as target proteins for several cell surface display systems (8,12,14,15,19,25). Of these, only yeast and E. coli have been employed for biocatalysis in an organic solvent at a moderate temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface display allows peptides and proteins to be displayed on the surfaces of microbial cells by fusing them with the anchoring motif through recombinant DNA techniques. A wide range of applications of the display technology include bioadsorption (15)(16)(17)(18)(19)(20), whole-cell biocatalyst (21)(22)(23)(24)(25)(26)(27), peptide library screening (28,29), live vaccine development (30)(31)(32), antibody production (33), and biosensors (34,35). Although cell attachment through cell surface display is not a well-known application, cell attachment through displaying peptides with binding affinity has been reported on chitin, cellulose, and gold substrates.…”
mentioning
confidence: 99%